A Comparison of the Damage Tolerance of AA7075-T6, AA2024-T3, and Boeing Space, Intelligence, and Weapons Systems AM-Built LPBF Scalmalloy - Rhys Jones; Daren Peng; Andrew Ang; Richard W. Aston; Nicole D. Schoenborn; Nam D. Phan (Aerospace, 2023)
This paper first presents the results of an experimental study into the damage tolerance of AA7075-T6, which is widely used in both fixed- and rotary-wing aircraft, space structures, and laser bed powder fusion (LBPF) Scalmalloy specimens built by Boeing Space, Intelligence, and Weapons Systems. To this end, four single edge notch AA7075-T6 specimens and four identical single edge notch LBPF Scalmalloy specimens were tested. The resultant crack growth curves reveal that Boeing Space, Intelligence, and Weapons Systems AM-built Scalmalloy is more damage tolerant than conventionally built AA7075-T6. This finding leads to the observation that the da/dN versus ΔK curves associated with Scalmalloy and conventionally manufactured AA2024-T3 are similar. These findings highlight the potential for Boeing Space, Intelligence, and Weapons Systems AM-built Scalmalloy to be used to extend the operational lives of military aircraft by the on-demand printing of limited-life Scalmalloy replacement parts.